Maritime Domain Awareness dan Maritime Deterrence dalam Penguatan Strategi Pertahanan Laut Indonesia di Kawasan Indo-Pasifik (Journal Keamanan dan Keselamatan Maritim, 2026)
ABSTRACTGreat-power competition, grey-zone operations, transnational crime, and vulnerabilities of critical infrastructure have increased the complexity of the Indo-Pacific maritime environment. As an archipelagic state located at the intersection of the Indian and Pacific Oceans, Indonesia requires the capacity to develop an accurate maritime situational picture while generating a credible deterrent effect. This study analyses the relationship between Maritime Domain Awareness (MDA) and maritime deterrence and formulates priorities for integrating both into Indonesia's maritime defence strategy. It applies a qualitative descriptive approach through a literature review and document analysis of 28 sources comprising national regulations, regional documents, maritime security reports, and recent scholarly publications. The findings demonstrate that MDA should not be reduced to radars, satellites, and vessel-tracking systems. It is a cognitive infrastructure that transforms data into understanding, early warning, and decision support. Maritime deterrence, meanwhile, requires capability, credibility, communication, and readiness to shape an adversary's calculations. Indonesia's principal gaps concern fragmented inter-agency data, system interoperability, analytical capacity, the connection between information centres and operational assets, and strategic communication. This article proposes a six-stage integration model comprising detection, understanding, decision, action, signalling, and assessment. Strengthening this model requires a national common operating picture, layered sensors, data-sharing protocols, rapid-response forces, evidence-based strategic communication, and regional cooperation that preserves Indonesia's strategic autonomy.